PENGEMBANGAN KECERDASAN SPRITUAL ANAK USIA DINI DI PAUD ARRAISYAH KOBA KABUPATEN BANGKA TENGAH - Qomariah, Nurul (ICEJ : Islamic Childhood Education Journal, 2022)
PAUD Arraisyah is one of the PAUD in Bangka Tengah which is based on Islamic values, so that in its application it is consistently carried out through learning activities and other habituation activities at school. This is done with the aim of forming a generation with good morals.This study uses a type of field research with a qualitative descriptive research method. Methods of data collection using structured interviews, non-participant observation and documentation. Meanwhile, the data analysis method uses data reduction steps, data presentation and conclusion drawing.The results showed that the development of children’s spiritual intelligence in PAUD Arraisyah was carried out through the method of playing cards with hijaiyah letters, the method of singing Islamic songs, the method of habituation of dhuha prayer and the method of role playing. Of the four methods carried out, it was assessed that they were able to develop children’s spiritual intelligence which was seen from the children being able to recite the Duha prayer readings, the children memorized several short suras, daily prayers and remembrance after prayers.